Effects on Setting, Strength, Moisture Resistance and Linear Changes of Sorel's Cement on Mixing Portland Cement as an Additive. Issue 2 (2009) - Mathur, Ritu; Chandrawat, M. P. S.; Sharma, Sanjay K.
Abstract : Magnesium oxysulphate cement (MOC, Magnesia / Sorel's Cement), discovered by Sorel S.T. in 1867 and has versatile cementing characteristics. It is prepared by the reaction of magnesium sulphate with magnesia in aqueous solution. Dolomite is used as inert filler to absorb the heat evolved during the exothermic formations of oxysulphate cement. Additives play an important role to modify the properties of Sorel's cement by nullifying the harmful effects of the impurities present in the matrix. Incorporation of Portland cement in increasing quantities in magnesium oxysulphate cement improves the compressive strength of the cement remarkably. Water tightness of Sorel's cement increases with the increase in quantities of the additive (15%, 20%). Portland cement accelerates initial setting process and retards final setting process of oxysulpahte cement. An insignificant contraction in the length of the trial beams after mixing Portland cement in oxysulphate cement was an encouraging finding of the study.